Psycholinguistic Genealogy: A Critical Reading of Its Roots, Paradigms, and Development of Knowledge - Aulia Maratu Dzikra; Dina Febrina; Hanifa Syahri; Wilsa Martiana; Aprijon Efendi (Al-Muyassar: Journal of Arabic Education, 2026)
Psycholinguistics is a discipline that studies the relationship between language and human mental processes, combining psychological and linguistic elements. This science came to be known in 1954, after criticism put forward by Noam Chomsky against structural linguistic theory and behavioral psychology. Psycholinguistics studies the process of language acquisition, language processing, and the relationship between language and the brain. Key concepts in psycholinguistics include the innate ability to acquire language (Language Acquisition Device), developed by Chomsky, as well as its relationship to psychological theories such as behaviorism and cognitivism. In addition, psycholinguistics is also relevant in language teaching, emphasizing the importance of understanding mental processes in language learning. Paradigms in psycholinguistics, including behavioristic, nativistic, cognitivistic, and socio-cognitive, provide different perspectives on understanding the way language is learned and processed. Research in psycholinguistics continues to evolve with the support of modern technologies in the field of cognition and neuroimaging.